The effects of Cannabis sativa extracts on melanoma cancer cells in vitro - Rostamian, Yasaman; University of Lethbridge. Faculty of Arts and Science (Lethbridge, Alta. :University of Lethbridge, Dept. of Biological Sciences, 2022)
Melanoma is the deadliest form of skin cancer, and its mortality continues to rise. Although early diagnosis and development of new treatments have improved melanoma prognosis, many patients develop resistance to current therapies. Research demonstrates that the main active ingredients of the cannabis plant, cannabinoids, have potential anti-cancer effects in different models of cancer. Cannabis plants, however, contain more than 545 secondary metabolites, which have shown to have medicinal potential and are believed to create an entourage effect when used together. The current study explores the anti-proliferative effects of ten cannabis extracts on melanoma cells in vitro. We discovered that studied cannabis extracts are cytotoxic for melanoma cells in a time- and dose-dependent manner and that high THC cannabis extracts exert higher cytotoxicity compared to their corresponding amount of THC alone. This anti-tumor activity may be via regulation of MAPK/ERK and PI3K/AKT pathway.
Keywords: Cannabis sativa; Cannabis extracts; Melanoma cells; Cannabis--Therapeutic use; Melanoma; Skin--Cancer--Treatment; Dissertations, Academic